A method for jamming waveform design in precision electronic warfare scenarios - Ke‐di Zhang; Qing‐song Zhou; Jing Wang; Jian‐yun Zhang; Zhi‐hui Li (IET Signal Processing)
Abstract In recent years, precision electronic warfare (PREW), an energy‐focussed delivery technology, has been used to solve a series of problems that currently limit traditional electronic warfare. A super‐sparse array of transmitters is used to concentrate the jamming energy as much as possible in the target area and reduce the jamming energy as much as possible in other specific protected areas. However, determining how to design jamming waveforms with jamming characteristics, such as covering the target work bandwidth, while ensuring that the energy transmission meets the requirements, is still an urgent problem. For the first time, this paper considers the task characteristics of PREW applications as constraint conditions. Through a first‐order Taylor expansion, the optimisation problem is approximately transformed into a convex sequential cone programming problem, and jamming waveforms are obtained through an iterative solution method. Experiments showed that the jamming waveforms designed by this algorithm meet the energy distribution requirements of PREW scenarios, and at the same time, the jamming waveforms emitted by each transmitter are superimposed in the jamming area to produce a signal that can cover the target work bandwidth. This method can achieve energy focussing on the space and frequency domains.